DEVELOPMENT OF INTERACTIVE E-MODULES BASED BY CANVA AND HEYZENE FLIPBOOK IN HIGH SCHOOL PHYSICS MATERIAL - Siboro, Asiroha; Sinon, Iriwi L.S.; Allo, Alberto Tangke; Mujasam, Mujasam (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2024)
The 21st century learning system is a digital era system where learning is no longer limited by space and time, and the media used must be more engaging and interactive. The purpose of this research is to develop an interactive e-modules based by canva and heyzen flipbook that are valid, practical, and effective in learning. The research method use is Research and Development (R&D) with as ADDIE model. This research uses observation, interviews, and questionnaires as data collection instruments. Based on the results results, the material validity test score was 92 %, the media validity test score was 88 %, the teacher feasibility test score was 91 %, and the student test score was 96,87 %, received  a positif response from the students. From the results of these scores can be concluded that the e-module for the topic of Work and Energi is highly valid, practical, and suitable for use.Keywords: Development of interactive e-module, Canva, Heyzine FlipbookAbstrakSistem pembelajaran abad 21 adalah sistem era digital dimana pembelajarannya tidak lagi dibatasi oleh ruang dan waktu serta media yang digunakan harus lebih menarik dan interaktif. Tujuan dari penelitian ini adalah mengembangkan e-modul interaktif berbantuan Canva dan Heyzen Flipbook yang valid, praktis dan efektif dalam pembelajaran. Metode yang digunakan adalah metode Research and Development (R &D) dengan model ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Penelitian ini menggunakan observasi, wawancara, dan angket sebagai instrumen pengumpulan data. Berdasarkan hasil penelitian diperoleh skor uji validitas materi sebesar 92 %, skor uji validitas media sebesar 88 %, skor uji kelayakan guru sebesar 91 %, dan skor uji coba peserta didik sebesar 96,87 % serta mendapat respon positif dari peserta didik. Dari hasil skor tersebut disimpulkan bahwa e-modul untuk materi Usaha dan Energi tergolong sangat valid, praktis, dan layak digunakan.Kata Kunci: Pengembangan e-modul Interaktif, Canva, Heyzine Flipbook